(untitled) (Research Announcements "Heritage BG", 2025)
The report briefly presents the path followed by Bulgarian scientists from the 1990s to today in the direction of using artificial intelligence (AI) in historical research. Emphasis is placed on the creation, the general functional scheme, the data structure, and the functionalities of the Bulgarian expert system for the identification and classification of ancient coins, PSAMS, as a new, modern way of analyzing numismatic material. References: Boteva-Boyanova, D. (2006). Obvarzanost mezhdu izobrazhenie i nadpis pri obrochni relefi na Trakiyskiya konnik: analiz na baza danni. In: Obraz i kult v drevna Trakiya. Aspekti na formiraneto na trakiyskiya obrazen ezik. (ed. D. Boteva-Boyanova). Faber, 182-222. Boteva-Boyanova, D. (2007). Obrochnite plochki na Trakijskija konnik kato znakova sistema (Analiz I interpretacija na baza danni). Avtoreferat na disertacija za poluchavane na nauchnata stepen “doktor na istoricheskite nauki. Sofia. Grozdanova, L. (2021). Digitalna numizmatika – inovativni perspektivi kym tradicionen izvor. In: Back to the Sources in Memory of the Editors of “Sources for the Ancient History and Geography of Thrace and Macedonia”, on the occasion of the 70th anniversary from the publication of the second extended version in 1949/ Jubilaeus VIII/2, 2021 (eds. P. Delev, D. Boteva-Boyanova, L. Grozdanova). Sofia, 63-70. Peter, U. (2021). Ot Momzen do Semantichnata mrezha/Semantic Web: Perspektivi pred numizmatichnite izsledwaniq w digitalnata mrezha – monetite na zapadnoto Chenomorsko krajbrezhie onlajn. In: Back to the Sources in Memory of the Editors of “Sources for the Ancient History and Geography of Thrace and Macedonia”, on the occasion of the 70th anniversary from the publication of the second extended version in 1949/ Jubilaeus VIII/2, 2021 (eds. P. Delev, D. Boteva-Boyanova, L. Grozdanova). Sofia, 175–192. Tomov, V., Grigorov, A., Tacheva, M. (1989). O nekotoryh primenenijah metodov I sredstv isskustvenogo intellekta v istorii. In: Sbornik trudov Vtorogo mejdunarodnogo nauchnogo seminara “Teoria i primenenie isskustvenogo intellekta” (Sozopol, 29 maja-2 junja 1989), 63-70. Tomov, V., Grigorov, A., Gerov, A., Tacheva, M., Prokopov, I. (1989). Ekspertnaja sistema razpoznavanija I klassifikacii monet I monetnih sokrovist. In: Sbornik trudov Vtorogo mejdunarodnogo nauchnogo seminara “Teoria i primenenie isskustvenogo intellekta” (Sozopol, 29 maja-2 junja 1989), 352-257. Besevliev, V. (1964). Spätgriechische und spätlateinische Inschriften aus Bulgarien. Berlin. Boteva, D. (2002). The Heros of the Thracian Iconic Narrative: A Data Base Analysis. In: Proceedings of the Eighth International Congress of Thracology. Thrace and the Aegean. September 2000. Vol. II. Sofia, 817-822. Boteva, D. (2006). Die Suche nach dem Kode der Weihereliefs einer schriftlosen Kultur. In: Zeichen in der Archäologie/Zeitschrift für Semiotik, Bd. 28/1 (ed. D. Boteva). Tübingen: Stauffenburg Verlag, 69-82. Boteva, D. (2007). Abbildende Darstellung des Thrakischen Reiters: Analyse einer Datenbank. – In: The Lower Danube in Antiquity (VI c. BC – VI c. AD). International Archaeological Conference, Bulgaria-Tutrakan, 2005 (ed. L. Vagalinski). Sofia, 201-215. Grigorov, A., Vassileva, V. (1994). Flexible Data Structures for representation of Text Descriptions of Coin Figures. – International Journal “Information Theories and Applications”, No. 2/3, 9-14. Grigorova, V. (1994). Kolonialbronze Münzen im Expertensystem zum Erkennen und Klassifikation. – Annotazioni Numismatiche, No. 13, 262-264. Grozdanova, L. (2018). A digital view on the coins of Pautalia from the hoard of Krepost (Haskovo region). In: Society, Kings, Gods. In memoriam Professoris Margaritae Tachevae/Jubilaeus VII 2018. (eds. D. Boteva-Boyanova, P. Delev, J. Tzvetkova). Sofia, 365–372. Grozdanova, L., Ivanova-Anaplioti, H. (forthcoming). Digital Numismatics from the User Perspective. In: Proceedings of the XVI International Numismatic Congress in Warsaw (forthcoming). Peter, U., Franke, C., Köster, J., Tolle, K., Gampe, S., Stolba, V. F. (2024). CORPUS NUMMORUM – A Digital Research Infrastructure for Ancient Coins. https://doi.org/10.5281/zenodo.10633905 Tomov, V., Sahno, S. (1985). Experimental System for Recognition and Classification of Archaeological Ceramics. In: Artificial Intelligence: Methodology, Systems, Applications: Proceedings of the International Conference on Artificial Intelligence: Methodology, Systems, Applications (AIMSA ‘84) Varna, Bulgaria, 17-20 September 1984. North Holland, 191-198. Tomov, V., Tacheva, M., Grigorov, A. (1987). ESIT-An Expert System for Analysis of Antique Historical-Geographical Texts about Ancient Thrace. In: Artificial Intelligence: Methodology, Systems, Applications: Proceedings of the International Conference on Artificial Intelligence: Methodology, Systems, Applications (AIMSA ‘86) Varna, Bulgaria, 16-19 September 1986. North Holland, 235-242. Tomov, V., Grigorov, A., Vakarelov, I. (1994). PSAMS – A Program System for archiving Coins and Coin treasures. – Annotazioni Numismatiche, No. 13, 258-261. Tomov, V., Grigorov, A., Vassileva, V., Grigorova, V., Prokopov, I. (1994). Artificial Intelligence Program System for Recognition, Classification and Archiving Coins. – International Journal “Information Theories and Applications”, No. 2/3, 3-8.